Pengembangan media manipulatif berbasis permainan ular tangga dalam pembelajaran matematika materi garis singgung lingkaran - HASNAH, NUR (Maliki Interdisciplinary Journal, 2025)
This study aims to develop a manipulative learning media based on the snakes and ladders game for teaching the topic of tangent lines to circles. The research used the Research and Development (R&D) method with the 4-D development model, consisting of Define, Design, Develop, and Disseminate. The define stage was conducted to tangent lines to circlesanalyze the learning needs and problems faced by students. The design stage included the creation of a manipulative media in the form of a beach-themed snakes and ladders game. The develop stage involved expert validation, limited trials, and effectiveness testing. Finally, the disseminate stage was carried out by applying the media in class XI-D IPS at MAN 3 Kediri. The results indicated that the developed snakes and ladders media is valid, practical, and effective in increasing student engagement and conceptual understanding in mathematics learning, particularly on the topic of tangent lines to circles.